Internationalizing multiculturalism : expanding professional competencies in a globalized world - Lowman, Rodney L. (American Psychological Association, 2013)
"This book is published by the largest association of psychologists in the world, but it was not written solely for psychologists. Because the volume is intended to address its focal issues with "every professional" in mind and from the perspectives of professionals in any country, the examples intentionally cut across professions to illustrate how the constructs apply in different professional contexts. Necessarily, the book emphasizes some professions (in particular, psychology, business, education) more than others, but the hope is that any professional interested in internationalizing understanding of multiculturalism will also find much in the book that is helpful. With such a broad intended audience and topic, the book is not intended to be a definitive treatise covering every aspect of its subject matter or the nuances of practice in every profession. Rather, it is written as an invitation to show the need for and potential of internationalizing professional practice. We have not covered every multicultural issue (e.g., there is no chapter on the increasingly important topic of age and ageism), and we have not covered every application. However, we have taken five of the most important major multicultural categories (race, gender, national origin, sexuality and gender identity, and religion and secularism) and tried to show why and how international perspectives matter in each of these areas. Similarly, the book addresses issues related to individuals, groups, organizations, education, mental health, and psychology to exemplify the practical application of these concepts to real-world professional practice"--Preface. (PsycINFO Database Record (c) 2012 APA, all rights reserved).